Addition of organochromium reagents to heteroaryl aldehydes. Synthesis of heteroaryl substituted bis-allyl ethers and homoallyl ethers - Servi, S; Topaloglu, C (Molecular Diversity Preservation International, 2004)
Heteroaryl substituted allyl and homoallyl alcohols were synthesised with two different method. Synthesis of bis-allyl ethers and homoallyl ethers were carried out via reaction of allyl bromide with allyl alcohols and homoallyl alcohols, respectively. [2.3]-Wittig Rearrangement reactions of heteroaryl substituted bis-allyl ethers were investigated using GC/MS techniques. In these reactions two unexpected products were isolated in high yield.
Keywords: Nozaki-Hiyama reaction; organochromium reagents; heteroaromatic aldehydes